Treatment of wastewater from sugarcane process industry by electrochemical and chemical process: Aluminum (metal and salt). (June 2017) - Sahu, Omprakash; Rao, Dubasi Govardhana; Gopal, Richa; Tiwari, Anurag; Pal, Dharm
Graphical abstract: Highlights: Treatment of agro-food industry waste water. Treatment by electrocoagulation and chemical coagulation. Optimization of effecting parameters. Experiment conducted both in batch and continuous with aluminum. Treated water up to dischargeable. Abstract: The sugarcane processing industry needs a large amount of water. It requires approximately 1.5–2 m 3 of water to process 1 t of sugarcane and generates 1-m 3 as wastewater. The aim of research work is to treat the sugar industry wastewater with electrocoagulation and coagulation process by batch and continuous modes. The results showed that by using aluminum electrode, 84% of COD reduction and 88% of color removal could be achieved at an optimum pH of 7.5, electrode distance of 20 mm, current density of 178 A m −2 and electrolyte concentration of 0.5 M. In continuous treatment, a maximum of 61% of COD and 65% of color removal were achieved. The combined treatment with electrocoagulation and coagulation results showed 98% COD and 99.5% of the color reduction under the optimum condition. The filtrate and sludge were analyzed by FTIR spectroscopy.